Esensi Delik Obstruction of Justice Dalam Konstruksi Hukum Pidana - Keysha, Saradiba; Abduh, Rachmad (Universitas Ekasakti, 2024)
Obstruction of justice is a criminal offense formulated in the Criminal Code to protect the judicial process so that it runs fairly and prevents manipulation. However, law enforcement against obstruction of justice in Indonesia is considered to be still weak due to several obstacles such as unclear article formulations, weak cooperation between related institutions, minimal internal supervision and lack of public understanding. Therefore, various comprehensive improvement efforts are needed both in terms of regulations, coordination between institutions, internal supervision, and public education so that enforcement of obstruction of justice laws can run effectively and optimally in Indonesia.